2021
DOI: 10.3390/ijms22168463
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondrial Dysfunction in Atrial Fibrillation: Translation to Druggable Target and Biomarker Discovery

Abstract: Atrial fibrillation (AF) is the most prevalent and progressive cardiac arrhythmia worldwide and is associated with serious complications such as heart failure and ischemic stroke. Current treatment modalities attenuate AF symptoms and are only moderately effective in halting the arrhythmia. Therefore, there is an urgent need to dissect molecular mechanisms that drive AF. As AF is characterized by a rapid atrial activation rate, which requires a high energy metabolism, a role of mitochondrial dysfunction in AF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 135 publications
(201 reference statements)
0
43
0
1
Order By: Relevance
“…In this study, we observed that rapid pacing led to atrial mitochondrial damage, which influence ATP production and GC activity as ATP can enhance GC activity (Duda, 2010). RAP leads to mitochondrial DNA damage in atrial myocytes and the impairment of mitochondrial oxidative phosphorylation function (Pool et al, 2021), it eventually result in the disorder of ATP synthesis and the imbalance of energy metabolism in atrial myocytes, which may be one of the reasons for the decrease of PGC activity. Therefore, the sensitivity of NPR-A to ANP and PGC activity decreased during RAP, resulting in reduced cGMP production.…”
Section: Discussionmentioning
confidence: 77%
“…In this study, we observed that rapid pacing led to atrial mitochondrial damage, which influence ATP production and GC activity as ATP can enhance GC activity (Duda, 2010). RAP leads to mitochondrial DNA damage in atrial myocytes and the impairment of mitochondrial oxidative phosphorylation function (Pool et al, 2021), it eventually result in the disorder of ATP synthesis and the imbalance of energy metabolism in atrial myocytes, which may be one of the reasons for the decrease of PGC activity. Therefore, the sensitivity of NPR-A to ANP and PGC activity decreased during RAP, resulting in reduced cGMP production.…”
Section: Discussionmentioning
confidence: 77%
“…In cardiomyocytes, the cytoskeleton is highly specialized, consisting of actin filaments, desmin (intermediate) filaments, and microtubules, interacting with membrane-associated proteins, sarcomeric and nuclear proteins, and proteins of the intercalated disk. This complex network, which also interacts with various organelles, including sarcoplasmic reticulum (SR), mitochondria, and the nucleus, plays an important role in the transmission of signals and the transport of (ubiquitinated) proteins within the proteostasis network [6,19,22] (Figure 2). Within the proteostasis network, especially the Emerging research findings indicate a prominent role of genetic variations mainly in ion channel and cytoskeletal (-associated) genes in driving AF [15].…”
Section: Key Role Of the Cytoskeletal Network In Cardiomyocyte Functionmentioning
confidence: 99%
“…However, metabolic syndrome (MS) is closely related to an increased morbidity of arrhythmia in various pathophysiological aspects ( Kumar and Gehi, 2012 ; Gawałko et al, 2021 ; Joseph et al, 2021 ; Pool et al, 2021 ). A large cohort study showed that metabolic factors including obesity, hypertension, low LDL-C level, and impaired fasting blood glucose level are closely related to new-onset atrial fibrillation (AF) ( Watanabe et al, 2008 ).…”
Section: Translation In Modern Medicinementioning
confidence: 99%